38th Plasmadynamics and Lasers Conference 2007
DOI: 10.2514/6.2007-4373
|View full text |Cite
|
Sign up to set email alerts
|

Development of Two-Fluid Magnetohydrodynamics Model for Non-Equilibrium Anisotropic Plasma Flows

Abstract: A multi-species magnetohydrodynamic (MHD) model based on an extended fluid dynamics description for each plasma species is proposed for the prediction of the flow and behavior of fully ionized non-equilibrium anisotropic plasmas. In particular, a two-fluid (ions and electrons) plasma model is described that makes use of a 10-moment or Gaussian anisotropic moment closure to model ion and electron species transport. The ion and electron moment equations are fully coupled to the complete set of Maxwell's equation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Despite the numerical difficulties of multi-fluid models, we have demonstrated that a high-order numerical scheme and the proposed boundary conditions, the simulation is able capture the plasma-sheath transition, being consistent with both the classical and kinetic theories. This work can be extended to more complex multi-fluid models that consider higher-order moments, including non-isotropic tensor [46] which can lead to instabilities at high-temperature sheaths [47]. The importance of writing the equations in conservation form, as opposed to other methods that solve for other nonconserved magnitudes such as velocity and temperature, is fundamental for finite volume methods.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the numerical difficulties of multi-fluid models, we have demonstrated that a high-order numerical scheme and the proposed boundary conditions, the simulation is able capture the plasma-sheath transition, being consistent with both the classical and kinetic theories. This work can be extended to more complex multi-fluid models that consider higher-order moments, including non-isotropic tensor [46] which can lead to instabilities at high-temperature sheaths [47]. The importance of writing the equations in conservation form, as opposed to other methods that solve for other nonconserved magnitudes such as velocity and temperature, is fundamental for finite volume methods.…”
Section: Discussionmentioning
confidence: 99%
“…This allows for more realistic modelling of the plasma. Presently several efforts are carried out in different countries to develop plasma numerical tools for several applications such as fusion, electric propulsion, active control over hypersonic vehicles: these efforts lead to a growing experience in CMFD field (see Park et al 1999, Kenneth et al 1998, Taku and Atsushi 2004, Cristofolini et al 2007, Miura and Groth 2007, MacCormack 2007, Yalim 2001, Giordano and D'Ambrosio 2004, Battista 2009. The chapter presented was carried out in the context of a research activity motivated by renewed interest in investigating the influence that electromagnetic fields can exert on the thermal and pressure loads imposed on a body invested by a high energetic flow.…”
Section: Introductionmentioning
confidence: 99%